Silicon Improves Rice Salinity Resistance by Alleviating Ionic Toxicity and Osmotic Constraint in an Organ-Specific Pattern - Guochao Yan; Xiaoping Fan; Miao Peng; Chang Yin; Zhuoxi Xiao; Yongchao Liang (Frontiers in Plant Science, 2020)
Salinity stress severely inhibits the growth of plant via ionic toxicity and osmotic constraint. Exogenous silicon (Si) can alleviate salinity stress, but the mechanisms behind remain unclear. To investigate the role of Si in alleviating ionic and osmotic components of salinity, rice (Oryza sativa L.) seedlings were grown hydroponically in iso-osmotic stress conditions developed from NaCl or polyethylene glycol (PEG). The effects of Si on the growth of shoot and root of rice under salinity and PEG-derived osmotic stress were evaluated and further compared using principal coordinate analysis (PCoA). We also analyzed the concentrations of Na, K, and compatible osmolytes, tissue sap osmotic potential, antioxidant enzymes activities, and the expression of aquaporin genes. Generally, Si significantly promoted shoot and root growth in rice exposed to both NaCl and PEG. PCoA shows that the Si-induced distance change under NaCl treatment was larger than that under PEG treatment in the shoot, while the Si-induced distance changes under NaCl and PEG treatments were at an equal level in the root. Under salinity, Si decreased Na concentration and Na/K ratio in the shoot but not in the root. However, Si decreased net Na uptake and increased root Na accumulation content. Osmotic potential was increased in the shoot but decreased in the root by Si addition. Si decreased soluble sugar and proline concentrations in the shoot but increased soluble sugar and soluble protein concentrations in the root. Besides, Si promoted shoot transpiration rate and root morphological traits. Although both NaCl and PEG treatments upregulated aquaporin gene expression, Si addition maintained the expression of OsPIPs under NaCl and PEG treatments at same levels as control treatment. Furthermore, Si alleviated oxidative damages under both NaCl and PEG by regulating antioxidant enzyme activities. In summary, our results show that Si improves salt stress tolerance in rice by alleviating ionic toxicity and osmotic constraint in an organ-specific pattern. Si ameliorates ionic toxicity by decreasing Na uptake and increasing root Na reservation. Si alleviates osmotic constraint by regulating root morphological traits and root osmotic potential but not aquaporin gene expression for water uptake, and promoting transpiration force but not osmotic force in shoot for root-to-shoot water transport.